Performance based regulation: a strategy to increase breastfeeding rates - Fernanda Cobo-Armijo; Sofía Charvel; Mauricio Hernández-Ávila (Instituto Nacional de Salud Pública, 2017)
The decreasing breastfeeding rate in México is of public health concern. In this paper we discus an innovative regulatory approach -Performance Based Regulation- and its application to improve breastfeeding rates. This approach, forces industry to take responsibility for the lack of breastfeeding and its consequences. Failure to comply with this targets results in financial penalties. Applying performance based regulation as a strategy to improve breastfeeding is feasible because: the breastmilk substitutes market is an oligopoly, hence it is easy to identify the contribution of each market participant; the regulation's target population is clearly defined; it has a clear regulatory standard which can be easily evaluated, and sanctions to infringement can be defined under objective parameters. Recommendations: modify public policy, celebrate concertation agreements with the industry, create persuasive sanctions, strengthen enforcement activities and coordinate every action with the International Code of Marketing of Breast-milk Substitutes.